Structural optimisation of diffusion driven degradation processes - Waschinsky, Navina; Barthold, Franz-Joseph; Menzel, Andreas (Technische Universität Dortmund, 2021)
In this article, we propose an optimisation framework that can contribute to the prevention of premature failure or damage to building structures and can thereby strengthen their longevity. We concentrate on structures that are contaminated by chemical substances and that have strong destructive effects on the material. The aim of this contribution is a mathematical algorithm that allows the optimisation of a structure exposed to chemical influences and thus the assurance of the static load capacity. To achieve this, we present a coupled mechanical-diffusion-degradation approach embedded in a finite element (FE) framework. Furthermore, we integrate an optimisation algorithm to reduce material degradation. In this paper, we establish shape optimisation of a structure with a gradient based optimisation algorithm.
Structural and multidisciplinary optimization;Bd 64. 2021, H. 2, S. 889-903
Keywords: Coupled problems; Mechanical diffusion coupling; Degradation; Shape optimisation; 690